Potential Benefits of Horizontal Wells for CO2 Injection to Enhance Storage Security and Reduce Leakage Risks - Marcos Vitor Barbosa Machado; Mojdeh Delshad; Kamy Sepehrnoori (Applied Sciences, 2023)
This study used numerical simulations of CO2 storage to identify the benefits of horizontal wells for geological carbon storage, such as enhancing CO2 trapped in porous media due to relative permeability and capillary hysteresis. Two injection schemes were tested: one using a vertical injector and the other employing a horizontal well. The results revealed two main findings. Firstly, the horizontal injection well effectively prevented or minimized CO2 penetration into the caprock across various sensitivity scenarios and over a thousand years of CO2 redistribution. Secondly, horizontal wells provided a safe approach to trapping CO2, increasing its entrapment as a residual phase by up to 19% within the storage site. This, in turn, reduced or prevented any unexpected events associated with CO2 leakage through the caprock. Additionally, the paper proposes a practical method for designing the optimal length of a horizontal well. This method considers a combination of two parameters: the additional CO2 that can be trapped using a horizontal well and the gravity number. In the case of the reservoir model of this study, a horizontal branch with a length of 2000 m was found to be the most effective design in enhancing CO2 entrapment and reducing CO2 buoyancy.